The poxvirus F17 protein counteracts mitochondrially orchestrated antiviral responses - Nathan Meade; Helen K. Toreev; Ram P. Chakrabarty; Charles R. Hesser; Chorong Park; Navdeep S. Chandel; Derek Walsh (Nature Communications, 2023)
Abstract Poxviruses are unusual DNA viruses that replicate in the cytoplasm. To do so, they encode approximately 100 immunomodulatory proteins that counteract cytosolic nucleic acid sensors such as cGAMP synthase (cGAS) along with several other antiviral response pathways. Yet most of these immunomodulators are expressed very early in infection while many are variable host range determinants, and significant gaps remain in our understanding of poxvirus sensing and evasion strategies. Here, we show that after infection is established, subsequent progression of the viral lifecycle is sensed through specific changes to mitochondria that coordinate distinct aspects of the antiviral response. Unlike other viruses that cause extensive mitochondrial damage, poxviruses sustain key mitochondrial functions including membrane potential and respiration while reducing reactive oxygen species that drive inflammation. However, poxvirus replication induces mitochondrial hyperfusion that independently controls the release of mitochondrial DNA (mtDNA) to prime nucleic acid sensors and enables an increase in glycolysis that is necessary to support interferon stimulated gene (ISG) production. To counter this, the poxvirus F17 protein localizes to mitochondria and dysregulates mTOR to simultaneously destabilize cGAS and block increases in glycolysis. Our findings reveal how the poxvirus F17 protein disarms specific mitochondrially orchestrated responses to later stages of poxvirus replication.